Uncovering mitochondrial defects in photoreceptors opens therapeutic opportunities for Stargardt disease - Simona Brillante; Mariagrazia Volpe; Anna Diana; Santiago Negueruela; Marta Molinari; Rosa Saurino; Eva Cipollaro; Elena Polishchuk; Erika Tenderini; Carla Damiano; Patrizia Tornabene; Roman Polishchuk; et al. (Proceedings of the National Academy of Sciences, 2026)
Stargardt disease type 1 (STGD1) is the most common hereditary macular degeneration. It is caused by mutations in ABCA4 , which result in the progressive degeneration of the retinal pigment epithelium (RPE), ultimately leading to photoreceptor loss. Despite extensive efforts, STGD1 currently lacks effective treatments. Here, we first identified mitochondrial defects in the photoreceptors of Abca4 −/− mice and STGD1 patient-derived retinal organoids. Specifically, we found reduced mitochondrial content, defective cristae morphology, and downregulation of OPA1, a critical regulator of mitochondrial integrity, demonstrating that photoreceptor defects in STGD1 also have a cell-autonomous origin, besides the RPE dysfunction. Importantly, we also demonstrated that correcting this pathological phenotype through the modulation of microRNAs 181a and b (miR-181a/b), key regulators of mitochondrial function, ameliorates the STGD1 phenotype. Indeed, genetic inactivation and adeno-associated viral vector-mediated silencing of miR-181a/b in STGD1 models restored OPA1 levels, improved mitochondrial phenotype, and reduced lipofuscin accumulation in the RPE. Our study demonstrates that mitochondrial dysfunction in photoreceptors is an important contributor to STGD1 pathology, opening promising therapeutic avenues for this disorder.